Bone impairment caused by AlCl3 is associated with activation of the JNK apoptotic pathway mediated by oxidative stress. (June 2018) - Yang, Xu; Yu, Kaiyuan; Wang, Haoran; Zhang, Haiyang; Bai, Chongsheng; Song, Miao; Han, Yanfei; Shao, Bing; Li, Yanfei; Li, Xinwei
Abstract: Exposure to aluminum (Al) inhibits bone formation, the principal mechanism possibly due to oxidative stress. However, little data is available that establishes the precise relationship. In this study, Wistar rats were exposed to 0 (GC), 0.4 (GL), 0.8 (GM) or 1.6 (GH) mg/L aluminum trichloride (AlCl3 ) in drinking water for 90 days, respectively. The concentrations of Al in serum and bone, serum markers of bone metabolism, bone mineral density (BMD) and body weight were measured. Histological changes within femurs were observed by H&E, ALP, and TRACP staining. Oxidative stress markers and JNK apoptotic pathway were detected in bone. The results indicate that AlCl3 exposure decreased BMD, numbers of ALP-positive osteoblasts and serum levels of bone formation markers (B-ALP, PICP and BGP), and caused damaged to the trabecular structure. Serum levels of bone resorption markers (TRACP-5b, CTX-I) and numbers of TRACP-positive osteoclasts increased in GL, but conversely, they decreased in GM and GH. In addition, AlCl3 caused oxidative stress, up-regulated expression of c-Jun and pro-apoptotic factors with increased p-JNK/JNK ratio and down-regulated expression of anti-apoptotic factor Bcl-2 in bone. Taken together, these results indicate that bone impairment caused by AlCl3 is associated with activation of the oxidative stress-mediated JNK apoptotic pathway. Graphical abstract: Highlights: AlCl3 exposure is detrimental to the balance of bone formation and resorption. Low doses of AlCl3, promotes osteoclast formation, high dose of AlCl3 causes the osteoclast apoptosis. Bone impairment caused by AlCl3 is associated with activation of the JNK apoptotic pathway mediated by oxidative stress.